The JAK1/JAK2 inhibitor ruxolitinib inhibits mediator release from human basophils and mast cells - Poto, Remo; Cristinziano, Leonardo; Criscuolo, Gjada; Strisciuglio, Caterina; Palestra, Francesco; Lagnese, Gianluca; Di Salvatore, Antonio; Marone, Gianni; Spadaro, Giuseppe; Loffredo, Stefania; Varricchi, Gilda (Frontiers in Immunology, 2024)
The Janus kinase (JAK) family includes four cytoplasmic tyrosine kinases (JAK1, JAK2, JAK3, and TYK2) constitutively bound to several cytokine receptors. JAKs phosphorylate downstream signal transducers and activators of transcription (STAT). JAK-STAT5 pathways play a critical role in basophil and mast cell activation. Previous studies have demonstrated that inhibitors of JAK-STAT pathway blocked the activation of mast cells and basophils. In this study, we investigated the in vitro effects of ruxolitinib, a JAK1/2 inhibitor, on IgE-and IL-3-mediated release of mediators from human basophils, as well as substance P-induced mediator release from skin mast cells (HSMCs).Ruxolitinib concentration-dependently inhibited IgE-mediated release of preformed (histamine) and de novo synthesized mediators (leukotriene C 4 ) from human basophils. Ruxolitinib also inhibited anti-IgE-and IL-3-mediated cytokine (IL-4 and IL-13) release from basophils, as well as the secretion of preformed mediators (histamine, tryptase, and chymase) from substance P-activated HSMCs. These results indicate that ruxolitinib, inhibiting the release of several mediators from human basophils and mast cells, is a potential candidate for the treatment of inflammatory disorders.